A Design and Implementation of Carbon Monoxide Toxic Gas Monitoring Device Based on Esp32 Master-Slave Using Fuzzy Logic Method in UNY Welding Workshop - Sony, Arya (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
Lack of awareness of welding workshop workers towards Occupational Health and Safety (K3) is a serious and high-risk problem for them. The danger of CO gas emissions from the welding process can cause serious toxic exposure that has the potential to cause long-term health and disease risks. Regulation of the Minister of Manpower Number 5 of 2018 concerning the Limitation of CO Gas Exposure of 25 ppm for 8 working hours per day. Workers are required to use Personal Protective Equipment (PPE) if the gas levels exceed the specified limits. This study discusses the problems in welding workshops by utilizing the MQ-135 gas sensor with the ESP32 microcontroller. The output of this tool is a 16x2 LCD screen to provide written warnings, a buzzer to provide sound warnings, and a DC fan controlled using fuzzy logic to neutralize the air in the welding area. The system works with a Master - Slave topology so that data transmission is carried out wirelessly which makes the layout of the tool more flexible. The results of the study indicate that the Air Quality Control Tool with the MQ-135 sensor using the ESP32 microcontroller has been designed efficiently. The ESP32 performed very well, achieving a 100% success rate for the required functions, although there was a small error rate of 17.71% compared to the Carbon Monoxide Alarm as a comparison. Testing showed good effectiveness, with communication between the master and slave devices taking an average of only 0.21 seconds. The ESP32's network connectivity quality achieved a 100% success rate over a wide range of distances and in the presence of obstacles.